Fostering Students’ Reading Comprehension Through Partner Reading Strategy - Pebriantika, Erlin (LPPM Institut Pendidikan Nusantara Global, 2024)
This study focused in implementing Partner Reading Strategy in improving students’ reading comprehension. The genre of text was limited to the descriptive text that becoming one of curriculum target for English language skills competence for grade 8th of SMPN 4 Taliwang, West Sumbawa Regency. By generating Classroom Action Based Research, 27 students were becoming sample toward this research. According to data analysis, this research found that the implementation of Partner Reading Strategy was claimed to improve student’s reading comprehension. This research was led to the Achievement Indicator by looking at the last cycle (Cycle II) achievement score as 76,86 and its categorization as Good. The implementation of Partner Reading Strategy also contributed to positive contribution into TL process as in; developed self-confident, activated in communication by sharing ideas each other, highly responded in taking feedback, developed social interaction between students and friends, and also teachers and their students. Therefore, the class situation became more fun and enjoyable for students and teacher. By meant that, the condition indirectly supported educational superiority and fostered student’s learning outcomes.